2014
DOI: 10.1590/abd1806-4841.20142874
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and cardiovascular risk factors in patients with psoriasis

Abstract: BACKGROUNDPsoriasis is a chronic inflammatory disease and its pathogenesis involves an interaction between genetic, environmental, and immunological factors. Recent studies have suggested that the chronic inflammatory nature of psoriasis may predispose to an association with other inflammatory diseases, especially cardiovascular diseases and metabolic disorders.OBJECTIVESTo describe the demographic, clinical, epidemiological, and laboratory characteristics of a sample of psoriasis patients; to assess the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 37 publications
3
42
0
2
Order By: Relevance
“…The prevalence of MetS in the present study was 50.0%. A single center study carried out by Baeta et al . in the southeastern region of Brazil ( n = 190 patients with PsO) observed a 44.9% prevalence of MetS, similar to our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of MetS in the present study was 50.0%. A single center study carried out by Baeta et al . in the southeastern region of Brazil ( n = 190 patients with PsO) observed a 44.9% prevalence of MetS, similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of MetS in the present study was 50.0%. A single center study carried out by Baeta et al 41 in the southeastern region of Brazil (n = 190 patients with PsO) observed a 44.9% prevalence of MetS, similar to our study. A case-control Brazilian study investigated research questions similar to ours regarding PsO comorbidities, specifically, the frequency of hypertension and MetS.…”
Section: Discussionsupporting
confidence: 91%
“…In some studies, the risk of CVD has been reported to be higher in patients with psoriasis. 1 , 5 , 9 17 However, in some other reports in overall examination and considering the whole psoriatic patients the risk of CVD, transient ischemic attacks, or cerebrovascular accidents remained unchanged between psoriatic patients and controls. 18 Furthermore, no association between psoriasis and metabolic syndrome has been observed in Korean psoriatic patients.…”
Section: Introductionmentioning
confidence: 88%
“…The impact on the quality of life may cause depression, which in turn negatively affects adherence to treatment. Based on a meta-analysis, the prevalence of depression in patients with psoriasis is 20-30% [3,29]. Severity of psoriasis was unrelated to depression risk [17].…”
Section: Expert Opinionmentioning
confidence: 99%